Pretreatment of lignocellulosic biomass: A review on recent advances. (August 2021) - Mankar, Akshay R.; Pandey, Ashish; Modak, Arindam; Pant, K.K.
Graphical abstract: Highlights: Lignocellulosic biomass is a clean energy source for biorefinery applications. Pretreatment is a key step for biomass transformation to valuable chemicals. Efficient and ecofriendly pretreatment approach to disintegrate biomass is needed. Recent advances in physical and chemical pretreatment approaches are discussed. Understanding of pretreatment mechanism is required for overcoming the challenges. Abstract: Depleting fossil reserves and growing energy needs have raised the demand for an alternative and clean energy source. The use of ubiquitously available lignocellulosic biomass for developing economic and eco-friendly large scale biorefinery applications has provided the much-needed impetus in this regard. The pretreatment process is a vital step for biomass transformation into added value products such as sugars, biofuels, etc. Different pretreatment approaches are employed to overcome the recalcitrance of lignocellulosic biomass and expedite its disintegration into individual components- cellulose, hemicellulose, and lignin. The conventional pretreatment methods lack sustainability and practicability for industrial scale up. The review encompasses the recent advances in selective physical and chemical pretreatment approaches such as milling, extrusion, microwave, ammonia fibre explosion, eutectic solvents etc. The study will allow a deeper understanding of these pretreatment processes and increase their scope as sustainable technologies for developing modern biorefineries.